The moderating role of emotional intelligence and HR digitalization on the relationship between compensation and employee job performance in Johor manufacturing sector - Al-Shameri, Ahmed Saleh Ahmed Saif; Omar, Siti Sarah; Alzoraiki, Mohammed; Milhem, Marwan; Ateeq, Ali (International Journal of Management and Sustainability, 2024)
This research examines the moderating role of emotional intelligence and HR digitalization on the relationship between compensation and employee job performance in Johor manufacturing sector. The manufacturing sector, which has contributed significantly to the Malaysian national GDP, was among the most affected sectors during the remote work movement caused by several Covid-19. One of the most critical aspects was managing human resources (HR) in remote work and the challenges faced by the employees working online. Drawing upon the Theory of Social Exchange and Ability model of Emotional Intelligence, this practical study investigated the influence of compensation (COM) on employee job performance (EJP) with the moderation of human resource digitalization (HRDi) and emotional intelligence (EI). A quantitative methodology based on online and hard-copy questionnaires was adopted. The population of this study consisted of management employees, such as directors, managers, executives, and administrators working in Johor manufacturing companies. A total of 318 responses was used in this study. Utilising SPSS and Smart PLS, the researcher analysed preliminary and pilot studies, data screening and cleaning procedures, exploratory factor analysis, as well as partial least squares structural equation modeling to assess the relationships among variables and test the hypotheses. The research findings demonstrated that compensation directly affects employee job performance. Meanwhile, human resource digitalization moderates the relationships between compensation and job performance of employees. In addition, emotional intelligence moderates the relationships between compensation and employee job performance. Policymakers are urged to encourage HR digitalization implementation and training on enhancing emotional intelligence. Besides, organizations should have plans on how to enhance their implementation of HR digitalization and improve emotional intelligence.